Study on a Novel Cold-Active and Halotolerant Monoacylglycerol Lipase Widespread in Marine Bacteria Reveals a New Group of Bacterial Monoacylglycerol Lipases Containing Unusual C(A/S)HSMG Catalytic Motifs - Li, Ping-Yi; Zhang, Yan-Qi; Zhang, Yi; Jiang, Wen-Xin; Wang, Yan-Jun; Zhang, Yi-Shuo; Sun, Zhong-Zhi; Li, Chun-Yang; Zhang, Yu-Zhong; Shi, Mei; Song, Xiao-Yan; Zhao, Long-Sheng; et al. (Frontiers in Microbiology, 2020)
Monoacylglycerol lipases (MGLs) are present in all domains of life. However, reports on bacterial MGLs are still limited. Until now, reported bacterial MGLs are all thermophilic/mesophilic enzymes from warm terrestrial environments or deep-sea hydrothermal vent, and none of them originates from marine environments vastly subject to low temperature, high salts and oligotrophy. Here, we characterized a novel MGL, GnMgl, from the marine cold-adapted and halophilic bacterium Glaciecola nitratireducens FR1064T. GnMgl shares quite low sequence similarities with characterized MGLs (lower than 31%). GnMgl and most of its bacterial homologs harbor a catalytic Ser residue located in the conserved C(A/S)HSMG motif rather than in the typical GxSxG motif reported on other MGLs, suggesting that GnMgl-like enzymes might be different from reported MGLs in catalysis. Phylogenetic analysis suggested that GnMgl and its bacterial homologs are clustered as a separate group in the monoglyceridelipase_lysophospholipase family of the Hydrolase_4 superfamily. Recombinant GnMgl has no lysophospholipase activity but could hydrolyze saturated (C12:0-C16:0) and unsaturated (C18:1 and C18:2) MGs and short-chain triacylglycerols, displaying distinct substrate selectivity from those of reported bacterial MGLs. The substrate preference of GnMgl, predicted to be a membrane protein, correlates to the most abundant fatty acids within the strain FR1064T, suggesting the role of GnMgl in the lipid catabolism in this marine bacterium. In addition, different from known bacterial MGLs that are all thermostable enzymes, GnMgl is a cold-adapted enzyme, with the maximum activity at 30°C and retaining 30% activity at 0°C. GnMgl is also a halotolerant enzyme with full activity in 3.5 M NaCl. The cold-adapted and salt-tolerant characteristics of GnMgl may help its source strain FR1064T adapt to the cold and saline marine environment. Moreover, homologs to GnMgl are found to be abundant in various marine bacteria, implying their important physiological role in these marine bacteria. Our results on GnMgl shed light on marine MGLs.